To Look at Things as if They Could Be Otherwise: Educating the Imagination - Anderson Sathe, Laurie (Text Matters: A Journal of Literature, Theory and Culture, 2014)
In this article I would like to argue that Paul Ricoeur can show us how a text matters in its ability to educate the imagination which, in turn, has the capacity to bring about change. The context of my argument is health care, the texts of concern are those written by a health care provider, Rachel Naomi Remen, and the subjects to be educated and transformed include the individual readers (e.g. students) and, ultimately, healthcare students and professionals alike. As a physician herself Remen configures both a personal story of her being healed and her professional story of providing care, in order to imagine new ways to health and healing more holistically. This holistic approach integrates the mind, body and spirit in the healing process. I gain support for applying Ricoeur’s theory of the imagination to Remen’s texts from Richard Kearney and Maxine Greene. Kearney and Greene focus on the productive role of the imagination for its transformative power within their own academic contexts of philosophy and of education, respectively. I gain from their extension of Ricoeurian and imaginative thinking to the texts of health care to look at healthcare as if it could be otherwise.